Conceptualisation and experiences of engaged citizenship as critical consciousness, transformative education and mutual joy: An autoethnography - Talbot, A.; McCann, C. (South African Journal of Higher Education, 2023)
In recent years, higher education institutions globally and in South Africa have begun to focus more on the educational potential of community-university engagement. As a result, many institutions of higher learning have been reimagining and debating the terms used to describe the engagement between students, academic staff and their community partners. At Rhodes University in Makhanda, there has been an active change in terminology, with previous “volunteerism” programmes renamed “engaged citizenship” opportunities. This article’s authors are current staff members and previous students at Rhodes University, whose university experiences were shaped by their involvement in the Rhodes University Community Engagement (RUCE) Division. Using an autoethnographic style, they reflect on their experiences as volunteers/engaged citizens. These stories and reflections serve to highlight how the term engaged citizenship better encapsulates the nature of the involvement of students who are actively involved in their communities: where these community engagement spaces provide mutual benefit and mutual joy, deep learning and platforms for individuals to direct their agency to socially just ends. Ultimately, these narratives aim to illustrate the deeply personal ways in which the practice of engaged citizenship has shaped the authors’ own growth and generated the holistic and transformative educational experience for which higher education institutions strive.